Study of sputtered tin schottky barrier diode for Gan-hemt applications - Li, Kang (2016)
During the past two decades, GaN-based high electron mobility transistor (HEMT) has been identified to be a very promising transistor that is able to realize the applications of high voltage, high frequency, and high temperature and has drawn much research interest around the world. More recently, GaN-on-Silicon technology using Si CMOS production line has attracted much attention as it will reduce the production cost significantly. However, conventional fabrication process utilizes Ni/Au to realize metal contacts including ohmic and Schottky contacts, which is prohibited in CMOS-compatible process due to cross-contamination issue. Hence, there is a need to develop gold-free ohmic and Schottky contacts to achieve the CMOS-compatible process. This dissertation specifically investigates the Schottky barrier height ( SBH) and the leakage current transport mechanism under reverse-biased condition of TiN Schottky contact. The SBH will be obtained from the results of I-V and C-V characterizations, and the reverse-biased leakage current mechanism will be investigated by applying two different emission models. The study of both the SBH and the current transport mechanism will promote the development of TiN gate and further help to realize the CMOS-compatible fabrication process.